PENERAPAN HUKUMAN DISIPLIN KEPADA WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS IIB MERAUKE YANG MELANGGAR TATA TERTIB - Ashari, Wanda (Animha Law Journal, 2024)
Displinary punishment is given to immates who violate the prison rules, in this case the immates who are suspected of violating the rules are reguired to conduct an intial examinition by the head of security before being subjectt odisciplinary punishment in accordance with article 12 paragraph (1) of the Ministerial Regulationand Human Rights. Number 6 of 2013 concerning the Order of the State Correctional and Detention Center. The purpose ofthis study is to find out and understand the implementation of disciplinary punishment for inmates who violate the rules at the Merauke Class IIB Penitentiary and to find out the obstacles and efforts faced by the Merauke Class IIB Prison in providing guidance toovercome disciplinary violations. This research was carried out using an empirical juridical method that sees legislation as a benchmark and looks at the facts that occur in the field, especially in Merauke. The data obtained is then processed with primary and secondary legal materials From the research results, it is explained that the  implementation of disciplinary punishment must be in accordance with applicable procedures. If the inmates commit a violation in the light level category, the prison officer will give a verbal warning and a statement is made and if the inmate commits a violation in the severe category, a BAP will be carried out (Minutes of Investigation). The obstacles faced by Class IIB Prisons are equipped with adequate facilities and infrastructure, factors from the inmates and the lack of prison personnel and the effort smade are verbal socialization and billboards are made to inform about obligations and prohibitions to inmates.